2014
DOI: 10.1007/s00253-014-5540-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased salinity improves the thermotolerance of mesophilic nitrification

Abstract: Nitrification is a well-studied and established process to treat ammonia in wastewater. Although thermophilic nitrification could avoid cooling costs for the treatment of warm wastewaters, applications above 40°C remain a significant challenge. This study tested the effect of salinity on the thermotolerance of mesophilic nitrifying sludge (34°C). In batch tests, 5 g NaCl L −1 increased the activity of aerobic ammonia-oxidizing bacteria (AerAOB) by 20-21 % at 40 and 45°C. For nitrite-oxidizing bacteria (NOB), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…These advantages apply not only to warm wastewaters but also to wastewaters on sites with excess heat available. A few lab-scale studies have explored the potential of thermophilic nitrification for wastewater treatment, but achieved no more than 40-42.5°C (Shore et al, 2012;Courtens et al, 2014a). Thus far, this is the first study describing a thermophilic nitrifying bioreactor at 50°C.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These advantages apply not only to warm wastewaters but also to wastewaters on sites with excess heat available. A few lab-scale studies have explored the potential of thermophilic nitrification for wastewater treatment, but achieved no more than 40-42.5°C (Shore et al, 2012;Courtens et al, 2014a). Thus far, this is the first study describing a thermophilic nitrifying bioreactor at 50°C.…”
Section: Discussionmentioning
confidence: 99%
“…Lopez-Vazquez et al (2014) recently reported nitrifying activity up to 50°C in mesophilic sludge from an industrial wastewater treatment plant after temperature shocking of mesophilic biomass (34°C) in short-term batch activity assays. However, the observations by Courtens et al (2014a) pointed out that prolonged exposure (48 h) of mesophilic biomass to a temperature shock can lead to a complete loss of nitrifying activity. To our knowledge, there is no description of nitrification at 50°C or above for an extended period of time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH of the residual water in the aquaponic systems presented an average value of 7.5 after passing through the tilapia tanks. After the biofilter, the pH was reduced to average values of 6.0 to 6.5, depending on the nitrification process, as described by Courtens et al (2014). During periodic samplings, the pH oscillated between 5.5 and 6.9, controlled and similar to those used by Van Rijn (2013).…”
Section: Resultsmentioning
confidence: 94%
“…Traditional denitritation/denitritation with removal of NO 2 À and/or NO 3 À and heterotrophic production of nitrogen gas can also affect TIN mass balance (Daigger, As mentioned earlier in Section 3.1.1, this is possible when high solids concentration and coarse bubble diffusion create a favorable environment for the formation of anoxic pockets where production of nitrogen gas occurs (McNamara et al, 2022). Finally, the TIN mass balance (Figure S3) could also be impacted by biological uptake of nitrogen through bacterial growth and likely accounts for a small portion (<5%) (Courtens et al, 2014). In our study, we focused on the fate of nitrogen at constant saturated DO, while future work should look at TN and other nitrogen species, such as N 2 O.…”
Section: Temperature Ph and Nitrogen Speciation Could Lead To Differe...mentioning
confidence: 99%